Effect of a randomized controlled trial on the surgical treatment of spinal metastasis, 2000 through 2010: A population‐based cohort study. Issue 6 (10th December 2013) - Kelly, Michael L.; Kshettry, Varun R.; Rosenbaum, Benjamin P.; Seicean, Andreea; Weil, Robert J.
<x xml:space="preserve">Abstract</x> BACKGROUND The effect of randomized controlled trials (RCT) on clinical practice patterns and patient outcomes is understudied. A 2005 RCT by Patchell et al demonstrated benefit for surgical decompression in patients with spinal metastasis (SpM). We examined trends in spinal surgery for patients with SpM before and after publication of the Patchell RCT. METHODS The Nationwide Inpatient Sample (NIS) was used to identify a 20% stratified sample of surgical SpM admissions to nonfederal United States hospitals from 2000 to 2004 and 2006 to 2010, excluding 2005 when the RCT was published. Propensity scores were generated and logistic regression analysis was performed to compare outcomes in pre‐ and post‐RCT time periods. RESULTS A total of 7404 surgical admissions were identified. The rate of spine surgery increased post‐RCT from an average of 3.8% to 4.9% surgeries per metastatic admission per year (P = .03). Admissions in the post‐RCT group were more likely to be non‐Caucasian, lower income, Medicaid recipients, and have more medical comorbidities and a greater metastatic burden (P < .001). Logistic regression of the propensity‐matched sample showed increased odds post‐RCT for expensive hospital stay (2.9; 95% confidence interval [CI] = 2.6‐3.4) and some complications, including neurologic (1.7; 95% CI = 1.1‐2.8), venous thromboembolism (2.8; 95% CI = 1.9‐4.2), and decubitis ulcers (15.4; 95% CI = 6.7‐34.5). However, odds for in‐hospital mortality decreased (0.6; 95% CI = 0.5‐0.8). CONCLUSIONS Surgery for SpM increased after publication of a positive RCT. A significantly greater proportion of patients with lower socioeconomic status, more comorbidities, and greater metastatic burden underwent surgery post‐RCT. These patients experienced more postoperative complications and higher in‐hospital charges but less in‐hospital mortality. Cancer 2014;120:901–908. © 2013 American Cancer Society.